Assessment of Patients' Satisfaction toward Nursing Care at Hemodialysis units - Shnishil, ali; Mansour, Khalida (Iraqi National Journal of Nursing Specialties, 2013)
Objectives: To assess patients' satisfaction to nursing care at hemodialysis units and determine the relationshipbetween patients' satisfaction and patients' demographic data.Methodology: A descriptive study was carried out at hemodialysis units of Baghdad teaching hospitals from Feb.4th, 2010 through Sep. 5th, 2010. A purposive (non-probability) sample of (150) patients ta hemodialysis units niBaghdad teaching hospitals was selected. The data were collected through the use of constructing questionnaireand by means of an interview technique with the patients; the questionnaire consists of two parts (1)demographic data (2) patients' satisfaction to nursing care. The validity of the study questionnaire wasdetermined through the panel of experts and the reliability of the study questionnaire was determined throughthe pilot study. Descriptive statistical analysis procedure (frequency, percentage and mean of score) andinferential analysis procedure (person correlation coefficient, chi-square test and t-test) were used for dataanalysis.Results: The findings of the study indicated that there is high satisfaction to clinical nursing care, communication/patient –nurse relationship and moderate satisfaction toward nursing health education. Not statisticalsignificant difference between (gender, age, educational status, marital status, occupational status, frequency ofhemodialysis and duration of hemodialysis). While there is a statistical significant difference between patients'occupational status and their satisfaction toward communication /patient –nurse relationship.Recommendations: Great emphasize should be directed toward the educational aspects of hemodialysis unit byproviding educational posters, guidelines, pamphlets and manuals.